Application of microcirculatory indicators in predicting the prognosis of patients with septic shock - Xiaoxu Ding; Yuanlong Zhou; Xin Zhang; Tao Sun; Na Cui; Shenghai Wang; Dan Su; Zhanbiao Yu (Heliyon, 2024)
Objective: The aim of this study is to investigate the predictive value of indicators associated with microcirculation, capillary refill time (CRT), perfusion index (PI), and mottling score, on the prognosis of patients with septic shock. Method: A retrospective clinical study was conducted encompassing 78 patients diagnosed with septic shock and admitted to the Department of Critical Care Medicine at our hospital from January 2019 to January 2022. The study collated the clinical data of these patients, focusing on macrocirculatory hemodynamic parameters and microcirculatory indices. The parameters of interest were recorded at 0, 6, 24, and 48 h post-admission, including heart rate, mean arterial pressure (MAP), venous-to-arterial carbon dioxide partial pressure difference, superior vena cava oxygen saturation, lactic acid (LAC), CRT, PI, and mottling score. The enrolled patients were stratified into two cohorts based on the 28-day mortality rate: a survival group and a mortality group. A non-parametric statistical test was employed to compare the CRT, PI, and mottling score between the two groups. Furthermore, the predictive value of these microcirculatory indicators for mortality in septic shock patients was assessed using receiver operating characteristic (ROC) curve analysis. This methodology allowed for the evaluation of the prognostic accuracy of CRT, PI, and mottling score as indicators for mortality in the context of septic shock. Results: The vasoactive drug dose, PI, LAC, mottling score, and CRT upon admission in the survival group were significantly better than those in the mortality group at hour 6 of treatment, hour 24 of treatment, and hour 48 of treatment (P < 0.05). The predictive value of the three microcirculatory indicators at various time points was highest for the Perfusion Index (PI) at 48 h of treatment, the mottling score at 24 h of treatment, and the Capillary Refill Time (CRT) upon admission. The Area Under the Curve (AUC) for PI at 48 h of treatment was 0.941 (0.885–0.996), with a sensitivity of 90.9 % and a specificity of 94.1 %. For the mottling score at 24 h of treatment, the AUC was 0.889 (0.805–0.972), with a sensitivity of 82.4 % and a specificity of 88.6 %. The AUC for CRT upon admission was 0.872 (0.788–0.956), with a sensitivity of 91.2 % and a specificity of 77.3 %. Among the three indicators: PI, mottling score, and CRT, PI at hour 48 of treatment had the highest predictive value for the prognosis of patients with septic shock. Conclusion: Microcirculatory indicators have specific predictive value for the prognosis of patients with septic shock.